2004
DOI: 10.1007/s00429-004-0433-y
|View full text |Cite
|
Sign up to set email alerts
|

The development of adrenal homolog of rainbow trout Oncorhynchus mykiss: an immunohistochemical and ultrastructural study

Abstract: In this work we describe the adrenal homolog of the rainbow trout Oncorhynchus mykiss during development. At the histological level, the interrenal primordium is clearly evident in larvae 25 days after fertilization (dpf), and the immunohistochemical reactions for tyrosine hydroxylase (TH) and phenylethanolamine-N-methyltransferase (PNMT), which mark the chromaffin cells, appear as early as 27 dpf. Both reactions are evident in cells localized in the head kidney and in some, probably migrating, cells close to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
7
0

Year Published

2006
2006
2020
2020

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 29 publications
(30 reference statements)
4
7
0
Order By: Relevance
“…The two types of granules were first mingled in the same cell and their separation into different cells occurred only at the end of the advanced period. Other authors reported similar characteristics in different species of reptiles (Doddamani 2000;Rupik 2002), amphibians (Accordi et al 1975;Accordi and Grassi Milano 1977) and fish (Gallo and Civinini 2005). The chromaffin cells had only scarce innervation at the beginning of development; nerve endings were frequently observed only at the end of it.…”
Section: Discussionsupporting
confidence: 50%
See 1 more Smart Citation
“…The two types of granules were first mingled in the same cell and their separation into different cells occurred only at the end of the advanced period. Other authors reported similar characteristics in different species of reptiles (Doddamani 2000;Rupik 2002), amphibians (Accordi et al 1975;Accordi and Grassi Milano 1977) and fish (Gallo and Civinini 2005). The chromaffin cells had only scarce innervation at the beginning of development; nerve endings were frequently observed only at the end of it.…”
Section: Discussionsupporting
confidence: 50%
“…In particular, their polymorphic shape and their long cytoplasmic projections could be related to their migrating fitness, by amoeboid movements. Similar characteristics have also been described in the adrenal of the rainbow trout Oncorhynchus mykiss (Gallo and Civinini 2005), the toad Bufo bufo (Accordi and Grassi Milano 1977) and the grass snake Natrix natrix (Rupik 2002).…”
Section: Discussionmentioning
confidence: 50%
“…A limited number of studies on the development of interrenal tissue during fish larval development can be found in the literature (Tanaka et al , 1995; Gallo & Civinini, 2005). In the case of S. senegalensis , the development of interrenal tissue at stage 4 may indicate a major change in the corticosteroidogenic activity at pre‐metamorphosis in parallel to the early development of the hypophysis.…”
Section: Discussionmentioning
confidence: 99%
“…Chromaffin cells could not be identified in this study, thus the potential production of catecholamines and their role in stress response cannot be discussed here. In rainbow trout Oncorhynchus mykiss (Walbaum 1792), chromaffin cells have been first observed later in development than the interrenal cells and lower in numbers (Gallo & Civinini, 2005).…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, higher adrenaline levels after hatching relative to previous stages were found in the head and heart tissues of rainbow trout larvae (Meyer and Sauerbier, 1977). In addition, nervous control of catecholamine secretion from chromaffin cells of trout was reported as early as pre-hatching stage 28 (Gallo and Civinini, 2005). Therefore, the higher adrenergic tone on heart rate can presumably be related to increasing levels of circulating catecholamines.…”
Section: The Development Of Cardiac Regulatory Controlmentioning
confidence: 96%